2003
DOI: 10.1074/jbc.m212312200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Differences in the Activation of Estrogen Receptor-α (ERα)- and ERβ-dependent Gene Expression by cAMP Signaling Pathway(s)

Abstract: Although increases in intracellular cAMP can stimulate estrogen receptor-␣ (ER␣) activity in the absence of exogenous hormone, no studies have addressed whether ER␤ can be similarly regulated. In transient transfections, forskolin plus 3-isobutyl-1-methylxanthine (IBMX), which increases intracellular cAMP, stimulated the transcriptional activities of both ER␣ and ER␤. This effect was blocked by the protein kinase A inhibitor H89 (N-(2-(p-bromocinnamylamino)-ethyl)-5-isoquinolinesulfonamide) and was dependent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 80 publications
2
44
0
1
Order By: Relevance
“…It had been shown that cAMP/PKA stimulates the recruitment of cyclin D1 to unliganded ERa (Lamb et al 2000) and of the coactivator SRC-1 to the unliganded chicken PR (Rowan et al 2000), but whether the latter is true for ERa and whether either cofactor is necessary for the response were not determined. In fact, a mutational analysis indicated that none of the known phosphorylation sites of SRC-1 is necessary (Coleman et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It had been shown that cAMP/PKA stimulates the recruitment of cyclin D1 to unliganded ERa (Lamb et al 2000) and of the coactivator SRC-1 to the unliganded chicken PR (Rowan et al 2000), but whether the latter is true for ERa and whether either cofactor is necessary for the response were not determined. In fact, a mutational analysis indicated that none of the known phosphorylation sites of SRC-1 is necessary (Coleman et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This does not exclude that cAMP/PKA could modulate certain ERb target genes through alternate mechanisms. It was demonstrated that activation of ERb by cAMP/PKA could be monitored in transfections with reporter genes containing promoter-proximal cryptic AP1 sites (Coleman et al 2003), but it should be emphasized that all of our reporter genes were devoid of these. Our results suggest that cAMP signaling would help to discriminate, at least at certain target genes, between ERa and ERb effects in cells that coexpress the two isoforms, and thereby to fine-tune estrogenic responses.…”
Section: Carm1 Is the Link Between Pka And Eramentioning
confidence: 99%
See 2 more Smart Citations
“…The expression plasmid for NCoR was provided by Dr M Bagchi (Zhang et al 1998). The expression plasmid for SMRT was provided by Dr B G Rowan (Coleman et al 2003). The expression plasmids for SRC-1 and SRA were provided by Dr B W O'Malley .…”
Section: Cell Culture Transient Transfection and Reporter Assaysmentioning
confidence: 99%